-------------------------------
mathm11a_02
-------------------------------
Solutions to Questions 4 - 6
-------------------------------
(4)
(a)
exp(x) = (sum from n = 0 to infinity) x^n / n!
(b)
A real series (sum from n = 1 to infinity) x_n converges if there is a number L such that [(sum] -> L as N -> infinity.
A real series (sum from n = 1 to infinity) x_n converges absolutely if (sum from n = 1 to infinity) |x_n| converges.
(c)
For any real nonzero x,
|x^(n + 1) / (n + 1)!| / |x^n / n!|
= |x| / (n + 1)
-> 0 as n -> infinity.
The series (sum from n = 0 to infinity) |x^n / n!| therefore converges by the ratio test. In other words, the series (sum from n = 0 to infinity) x^n / n! converges absolutely.
(d)
Theorem about multiplication of series
Suppose that (sum from n = 0 to infinity) a_n and (sum from n = 0 to infinity) b_n are absolutely convergent real series. Then
[(sum] * [(sum]
= (sum from n = 0 to infinity) c_n
where
c_n = (sum from i = 0 to n) a_i b_(n - i)
--
By the theorem,
exp(x)exp(y) = (sum from n = 0 to infinity) c_n
where
c_n
= (sum from i = 0 to n) [x^i / i!][y^(n - i) / (n - i)!]
= (1/n!) (sum from i = 0 to n) nCi x^i y^(n - i)
= (1/n!) (x + y)^n . . . . . using the binomial theorem
So
exp(x)exp(y)
= (sum from n = 0 to infinity) (1/n!)(x + y)^n
= exp(x + y)
(e)
For any x >= 0,
exp(x)
= 1 + x + x^2/2 + (sum from n = 3 to infinity) x^n / n!
>= 1 + x + x^2/2 . . . . . because x^n / n! >= 0 for all n >= 3
--
Method 1 (not using the hint)
For any x <= 0,
(d/dx) [(1 + x) - exp(x)] = 1 - exp(x) >= 0
But (1 + x) - exp(x) = 0 when x = 0. So for any x <= 0,
(1 + x) - exp(x) <= 0
For any x <= 0,
(d/dx) [(1 + x + x^2/2) - exp(x)] = 1 + x - exp(x) <= 0
But (1 + x + x^2/2) - exp(x) = 0 when x = 0. So for any x <= 0,
(1 + x + x^2/2) - exp(x) >= 0
exp(x) <= 1 + x + x^2/2
Method 2 (using the hint)
For any x with -1 <= x <= 0,
exp(x) = 1 + x + x^2/2 + x^3 * [ 1/3! + x/4! + x^2/5! + x^3/6! + ... ]
and
1/3! + x/4! + x^2/5! + x^3/6! + ...
>= 1/6 - (1/4! + 1/6! + 1/8! + 1/10! + ...)
= 1/6 - [ (1/2)(exp(1) + exp(-1)) - 1 - 1/2 ]
= 5/3 - (1/2)(exp(1) + exp(-1))
>= 0
and so, since also x^3 <= 0,
exp(x) <= 1 + x + x^2/2 . . . . . (1)
For any x <= -1,
1 + x + x^2/2
= 1/2 + (1/2)(x + 1)^2
>= 1/2 + 0
= 1/2
>= exp(-1)
>= exp(x) . . . . . (2)
(1) and (2) together show that, for any x <= 0,
exp(x) <= 1 + x + x^2/2
--
(5)
(a)
f: R -> R is continuous at a c in R if: for any epsilon > 0 there is a delta > 0 such that |f(x) - f(c)| < epsilon for all x with |x - c| < delta.
(b)
Intermediate Value Theorem
Let f: R -> R be continuous. Suppose that p and q are in R, with p < q. Let k be any number between f(p) and f(q). Then there is an L in [p, q] such that f(L) = k.
Proof (by repeated bisection)
Without loss of generality, we assume that f(p) <= f(q). Then f(p) <= k <= f(q). Let a_1 = p and b_1 = q. Then f(a_1) <= k <= f(b_1).
Let c_1 be the midpoint (a_1 + b_1)/2 of [a_1, b_1].
(i) If f(c_1) <= k then let [a_2, b_2] be the right-hand half [c_1, b_1] of [a_1, b_1].
(ii) If f(c_1) > k then let [a_2, b_2] be the left-hand half [a_1, c_1] of [a_1, b_1].
Then f(a_2) <= k <= f(b_2).
Now repeat. Let c_2 be the midpoint (a_2 + b_2)/2 of [a_2, b_2].
(i) If f(c_2) <= k then let [a_3, b_3] be the right-hand half [c_2, b_2] of [a_2, b_2].
(ii) If f(c_2) > k then let [a_3, b_3] be the left-hand half [a_2, c_2] of [a_2, b_2].
Then f(a_3) <= k <= f(b_3).
Continuing in this way we get a nested sequence [a_1, b_1], [a_2, b_2], [a_3, b_3], ... of intervals such that:
(i) for all i, f(a_i) <= k <= f(b_i);
(ii) (a_i) is increasing and (b_i) is decreasing;
(iii) b_i - a_i = (b_1 - a_1) / 2^(i - 1) -> 0 as i -> infinity.
(a_i) converges because it is increasing and bounded above. Let L be the limit. Since b_i - a_i -> 0 as i -> infinity, we also have b_i -> L as i -> infinity.
Since f is continuous at L, and a_i -> L as i -> infinity,
f(a_i) -> f(L) as i -> infinity . . . . . (1)
[Proof of (1). Suppose that we are given an epsilon > 0. By the definition of continuity, there is a delta > 0 such that |f(x) - f(L)| < epsilon for all x with |x - L| < delta. By the definition of a limit, there is a positive integer N such that |a_i - L| < delta for all i >= N. Putting those two statements together, |f(a_i) - f(L)| < epsilon for all i >= N.]
Similarly,
f(b_i) -> f(L) as i -> infinity . . . . . (2)
Since f(a_i) <= k <= f(b_i) for all i, it follows from (1) and (2) that f(L) = k.
(c)
Define a continuous function g: R -> R by g(x) = f(x) - f(x + 1). Then g(0) = f(0) - f(1) = f(2) - f(1) = -[f(1) - f(2)] = -g(1). So either g(0) and g(1) are both zero, or one is positive and the other negative. The Intermediate Value Theorem implies that there is a y in [0, 1] such that g(y) = 0. Then f(y) = f(y + 1).
--
(6)
(a)
Suppose that f is not bounded. Then there is a sequence (x_n) in [a, b] with |f(x_n)| >= n for all n. By the Bolzano-Weierstrass Theorem, (x_n) has a convergent subsequence (x_n(i)). Let L be the limit of the subsequence. Then L is in [a, b]. Since f is continuous at L, f(x_n(i)) -> f(L) as i -> infinity. That is a contradiction -- because |f(x_n(i))| >= n(i) >= i for all i, f(x_n(i)) can't converge to anything as i -> infinity. So f is bounded.
(b)
By definition of the supremum, there is a sequence (x_n) in [a, b] with f(x_n) -> M as n -> infinity. By the Bolzano-Weierstrass Theorem, (x_n) has a convergent subsequence (x_n(i)). Let L be the limit of the subsequence. Then L is in [a, b]. Since f is continuous at L, f(x_n(i)) -> f(L) as i -> infinity. Since any subsequence of a convergent subsequence converges to the same limit, f(x_n(i)) -> M as i -> infinity. So f(L) = M.
(c)
f/g is a continuous function on [a, b]. By (a), f/g is bounded. So there is a number c such that |f(x)/g(x)| <= c for all x in [a, b]. So f(x) <= c g(x) for all x in [a, b].